Peningkatan Pelayanan Perizinan Online Melalui Inovasi Aplikasi Surabaya Single Window (SSW) Alpha - Diana Hertati; Binti Azizatun Nafi’ah; Katerina Bataha; Very Y. Londa; Donald K. Monintja (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In order to maximise public services as a support system for government administration, ongoing innovation is needed to raise the standard of public services. This study uses a qualitative methodology that involves creating a complex description, looking up words, compiling in-depth reports from respondents' perspectives, and studying real-world scenarios linked to enhancing online licencing services in the city of Surabaya via the SSW Alfa application programme. Research methods with qualitative descriptive and study focus include relative advance, Compatibility, Complexity, Trialability and Observability. Data analysis is based on the interactive data model from Miles and Huberman which consists of three activity flows that occur simultaneously, namely: data condensation, data presentation, and verification withdrawal. The results of the study show that SSW Alpha is based on: 1) Relative Advantage, the community is given the advantage of having easy access to permits; 2) Compatibility, there is a discrepancy in the flow of licensing and authority signing with previous innovations, therefore old innovations are no longer used; 3) Complexity, still complicated and trouble occurs and there are still incomplete files; 4) Triability, through the trial stages before the application is launched to the public; 5) Observability, making it easy for the public to observe and monitor the permit filing process and the convenience of officials to easily obtain licensing data.